Efficacy and safety of canagliflozin in patients with type 2 diabetes mellitus from Latin America. (3rd March 2016) - Lavalle-González, Fernando J.; Eliaschewitz, Freddy G.; Cerdas, Sonia; Del Pilar Chacon, Maria; Tong, Cindy; Alba, Maria
Abstract: Objective: This post hoc analysis evaluated the efficacy and safety of canagliflozin, a sodium glucose co-transporter 2 inhibitor, in patients with type 2 diabetes mellitus (T2DM) from Latin America. Research design and methods: Analyses were performed in subgroups of patients from Latin America based on data from three individual, 26-week, placebo-controlled studies of canagliflozin (monotherapy [ n = 116/584], add-on to metformin [ n = 199/918], and add-on to metformin plus sulfonylurea [ n = 76/469]) and three individual, 52-week, active-controlled studies of canagliflozin (add-on to metformin versus sitagliptin [ n = 240/1101], add-on to metformin versus glimepiride [ n = 155/1450], and add-on to metformin plus sulfonylurea versus sitagliptin [ n = 156/755]). Main outcome measures: Changes from baseline in HbA1c, body weight, and systolic blood pressure (BP) with canagliflozin 100 and 300 mg versus placebo or active comparator (i.e., sitagliptin or glimepiride) were evaluated in the overall study populations and Latin American subgroups. Safety was assessed based on adverse event (AE) reports. Results: Canagliflozin 100 and 300 mg provided reductions in HbA1c, body weight, and systolic BP across studies in patients from Latin America that were generally similar to those seen in the overall populations of patients with T2DM. The AE profile in patients from Latin America was equivalent to that in the overall populations; higher rates of genital mycotic infections and osmotic diuresis–related AEs were seen with canagliflozin versus comparators. Limitations of this study include the post hoc analysis of data and the small sample size of patients from Latin America. Conclusion: Canagliflozin improved glycemic control, reduced body weight and systolic BP, and was generally well tolerated in patients with T2DM from Latin America. Clinical trial registration: NCT01081834; NCT01106677; NCT01106625; NCT00968812; NCT01137812.